2016
DOI: 10.1140/epjc/s10052-016-4069-x
|View full text |Cite
|
Sign up to set email alerts
|

The cosmic ray test of MRPCs for the BESIII ETOF upgrade

Abstract: In order to improve the particle identification capability of endcap time-of-flight (ETOF) at Beijing Spectrometer III, it is proposed to upgrade current ETOF detector with multi-gap resistive plate chamber (MRPC) technology aiming at extending ETOF overall time resolution to be 80-100 ps for π 's. The new ETOF system including MRPC detectors, front end electronics, CLOCK module, fast control boards and time-to-digital conversion modules, was built up and underwent 3-month cosmic ray test. The main purposes of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Over the past decade, advanced nanoscale system-mediated drug delivery has received tremendous attention for the treatment of a myriad of chronic diseases, [12][13][14][15][16][17][18][19][20][21][22][23] most notably cancer, owing to the complexity of tumor biology, where untamed cell growth and protein transcription contribute to highly disorganized vasculature and congested extravascular environments (also known as the enhanced permeation and retention, or EPR, effect). 24,25 With nanoparticle (NP) technology, it may be possible to (1) achieve delivery of poorly water-soluble candidates, (2) protect cargos from premature degradation or detoxification, (3) control pharmacokinetic and biodistribution profiles, (4) enrich drug delivery in a tissueor cell-specific manner, and (5) improve intracellular penetration.…”
mentioning
confidence: 99%
“…Over the past decade, advanced nanoscale system-mediated drug delivery has received tremendous attention for the treatment of a myriad of chronic diseases, [12][13][14][15][16][17][18][19][20][21][22][23] most notably cancer, owing to the complexity of tumor biology, where untamed cell growth and protein transcription contribute to highly disorganized vasculature and congested extravascular environments (also known as the enhanced permeation and retention, or EPR, effect). 24,25 With nanoparticle (NP) technology, it may be possible to (1) achieve delivery of poorly water-soluble candidates, (2) protect cargos from premature degradation or detoxification, (3) control pharmacokinetic and biodistribution profiles, (4) enrich drug delivery in a tissueor cell-specific manner, and (5) improve intracellular penetration.…”
mentioning
confidence: 99%
“…Females had much higher levels of hepatic betaine, and betaine can exert antifibrotic effects. [ 32 ] In an earlier report, we had also observed that hepatic betaine was lower in males and in FD mice. [ 8 ] Increased betaine would allow females to maintain methylation at higher levels, compared to males.…”
Section: Discussionmentioning
confidence: 75%
“…Efficient preprocessing and segmentation of point cloud data and integrating different sensor data for comprehensive canopy characterization remain research challenges. Future research should focus on improving algorithms for specific operational environments, developing real-time processing algorithms, and investigating multi-source data fusion, such as integrating with inspection vehicles for yield estimation [53] and fusing with image data for volume prediction [54]. These improved algorithms can be integrated into intelligent agricultural management systems to support fine management, precision fertilization, and pest control applications.…”
Section: Data Availability Statementmentioning
confidence: 99%